RESEARCH ON THE INCIDENCE OF MALIGNANT TESTICULAR TUMORS IN UKRAINE AND SUMY REGION - Brusovtsov D.; Lуndіn M.; Sikora V.; Hyriavenko N.; Romaniuk A. (Eastern Ukrainian Medical Journal, 2020)
Oncological incidence of testicular cancer is the current medical and social problem in Ukraine and in the world. Despite the relatively low incidence rate for this pathology, it is of fundamental importance for clinicians, since it is the most common type of malignant tumors in young men of working age (15–45 years). In particular, the incidence of testicular cancer in Sumy region slightly differs from the national average. That is why the objective of our study was to analyze the level of testicular neoplasia among the population of Sumy region and Ukraine in 2011–2019, as well as to compare them. Based on the obtained data, Sumy region is included in the group of regions of Ukraine with an over-threshold incidence of testicular cancer. Statistical data analysis showed a tendency to a decrease of the overall incidence of testicular cancer among the adult population in Ukraine during the study period (on average, 2.55 per 100,000 population). At the same time, in Sumy region, there was a gradual increase in the frequency of cases of this oncopathology in men with the highest indicators reached in 2017 (4.33 per 100,000 population). Consequently, in Ukraine, this pathology affected men mainly at the age of 35–39. However, it is should be noted that the age range of morbidity in Sumy region was somewhat broader and mainly affected the population aged 30–39, and, in some years –men at the age of 20–29. It was established that testicular cancer affects the pediatric population, although it is extremely rare. Considering that seminoma is the most common type of testicular tumors, we focused on an in-depth study of its morphological features. Statistical data analysis revealed a link between the incidence of testicular cancer and the age of the male population. An important element of the research is the study of etiopathological factors that affect the growth of the degree of involvement, caused by this pathology.